Health anxiety in medical employees: A multicentre study. Issue 10 (October 2019) - Chen, Qingsong; Zhang, Yuqun; Zhuang, Dongyun; Mao, Xueqin; Mi, Guolin; Wang, Dijuan; Du, Xiangdong; Yi, Zhenghui; Shen, Xinhua; Sui, Yuxiu; Li, Huajie; Cao, Yin; et al.
Objective: The aim of this study was to explore health anxiety (HA) in a sample of hospital medical employees and to identify factors that influence HA. Methods: A consecutively recruited sample of 1702 medical employees with or without HA was obtained from 13 hospitals across China. Participants' demographic and clinical characteristics were collected using a standardized protocol and data collection procedure. Subjects were divided into a HA and non-HA group according to their scores on the Chinese version of the Short Health Anxiety Inventory. Comparisons between groups were conducted and binary logistic regression was used to identify risk factors of HA. Results: Total HA prevalence was 30.14%. There were significant differences between the HA and non-HA groups in number of working years, hospital category, sex, marital status, family income, personality, physical disease and education degree. Working in a specialist hospital, being female, being married, low income, introversion, graduate education or above and presence of physical disease were risk factors of HA. Conclusions: HA is common in medical employees. More investigation of the long-term impact of HA is warranted.